2014
DOI: 10.1155/2014/394847
|View full text |Cite
|
Sign up to set email alerts
|

Calabash Chalk's Geophagy Affects Gestating Rats' Behavior and the Histomorphology of the Cerebral Cortex

Abstract: Introduction.Calabash chalk contains heavy metals, and this lead to this study on the effect of this chalk on the behavior and the histomorphology of the cerebral cortex of gestating rats.Material & Methods.24 female rats were equally divided into 4 groups and were mated at preostrous with the males. The day after mating was designated as day 1 of gestation. On gestation days 7–20, groups 1, 2, 3, and 4 animals were treated with 1 mL of distilled water, and 1 mL (200 mg/kg), 2 mL (400 mg/kg), and 3 mL (600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…In conclusion, consumption of calabash chalk diet impairs locomotion and social behavior in mice. The major components of the calabash chalk such as lead and arsenic cross the blood-brain barrier to cause different effects including neurotoxicity in different parts of the brain (Cleveland et al., 2008; Ekong et al., 2014). While not ruling out the effects of other metals and micro organisms contained in the calabash chalk, it is possible that neurobehavioural deficits observed in this present study may be associated with the neurotoxicity of lead and arsenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, consumption of calabash chalk diet impairs locomotion and social behavior in mice. The major components of the calabash chalk such as lead and arsenic cross the blood-brain barrier to cause different effects including neurotoxicity in different parts of the brain (Cleveland et al., 2008; Ekong et al., 2014). While not ruling out the effects of other metals and micro organisms contained in the calabash chalk, it is possible that neurobehavioural deficits observed in this present study may be associated with the neurotoxicity of lead and arsenic.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies on calabash chalk revealed hepatic sinusoidal enlargements, gastrointestinal damaging and anaemic effects (Ekong et al., 2014). Lead and even arsenic constituents of calabash chalk have been reported to be associated with nervous and brain damages as well as learning and behavioural dysfunctions in animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…The nonsalted clay beverage samples used for this study were purchased in large quantities from supermarkets at Ikenegbu, Owerri, Imo State, Nigeria. The clay beverage was reduced to a fine powder using a manual grinder and dissolved in distilled water [ 15 ]. Due to its partial miscibility, the mixture was compulsorily stirred prior to oral gavage using a gastric tube.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant women cite ethnobotanical uses, such as intended amelioration of depression, early morning vomiting, nausea, and heartburn as the major predisposing factors to clay beverage consumption [ 12 ]. Some reports in the literature have associated clay beverage consumption to altered liver parenchyma and enlarged sinusoids, the lysis of erythrocytes, intestinal hemorrhage, bone demineralization, and gestational neurotoxicities [ 13 , 14 , 15 ]. Notwithstanding the paucity of information regarding the comprehensive biological effects of clay beverage, particularly during pregnancy, there are authoritative constraints with regard to dispelling or encouraging the practice of clay beverage consumption.…”
Section: Introductionmentioning
confidence: 99%
“…4 Reports show that it occurs with animals, as well as humans, in both sexes, and in all races; 5 in UK it is associated with immigrants from South Asia [6][7][8] and West African. 9,10 Geophagy, although often seen in rural or preindustrial settings among children and pregnant women 11 is not limited to any particular age or time. 12 Clay consumption has been reported to be associated with pregnancy, and some women eat clay to eliminate nausea.…”
Section: Introductionmentioning
confidence: 99%